Plant effects on microbiome composition are constrained by environmental conditions in a successional grassland - Mészárošová, Lenka; Kuťáková, Eliška; Kohout, Petr; Münzbergová, Zuzana; Baldrian, Petr (Environmental microbiome, 2024)
BACKGROUND: Below-ground microbes mediate key ecosystem processes and play a vital role in plant nutrition and health. Understanding the composition of the belowground microbiome is therefore important for maintaining ecosystem stability. The structure of the belowground microbiome is largely determined by individual plants, but it is not clear how far their influence extends and, conversely, what the influence of other plants growing nearby is. RESULTS: To determine the extent to which a focal host plant influences its soil and root microbiome when growing in a diverse community, we sampled the belowground bacterial and fungal communities of three plant species across a primary successional grassland sequence. The magnitude of the host effect on its belowground microbiome varied among microbial groups, soil and root habitats, and successional stages characterized by different levels of diversity of plant neighbours. Soil microbial communities were most strongly structured by sampling site and showed significant spatial patterns that were partially driven by soil chemistry. The influence of focal plant on soil microbiome was low but tended to increase with succession and increasing plant diversity. In contrast, root communities, particularly bacterial, were strongly structured by the focal plant species. Importantly, we also detected a significant effect of neighbouring plant community composition on bacteria and fungi associating with roots of the focal plants. The host influence on root microbiome varied across the successional grassland sequence and was highest in the most diverse site. CONCLUSIONS: Our results show that in a species rich natural grassland, focal plant influence on the belowground microbiome depends on environmental context and is modulated by surrounding plant community. The influence of plant neighbours is particularly pronounced in root communities which may have multiple consequences for plant community productivity and stability, stressing the importance of plant diversity for ecosystem functioning.